Colon Rectal Liver Metastases: The Role of the Liver Transplantation in the Era of the Transplant Oncology and Precision Medicine - Finotti, Michele; Vitale, Alessandro; Gringeri, Enrico; D'Amico, Francesco Enrico; Boetto, Riccardo; Bertacco, Alessandra; Lonardi, Sara; Bergamo, Francesca; Feltracco, Paolo; Cillo, Umberto (Frontiers in Surgery, 2021)
Liver metastases development in colon rectal cancer has a strong impact on patient overall survival, with a 5-years survival of 5% with palliative treatment. Surgical resection combined with pharmacological treatment can achieve a 5-year overall survival of 31–58%. However, in only 20% of patients with colon rectal liver metastases (CRLM) liver resection is feasible. In highly selected patients, recent trials and studies proved that liver transplantation for non-resectable CRLM is a surgical option with an excellent long term overall survival. The aim of this paper is to review the indications and outcome of liver transplantation for CRLMs, with a special focus on the immunosopressive therapy and the management of local and extra hepatic recurrence after liver transplantation.